'It's sometimes hard to tell what patients are playing at': How healthcare professionals make sense of why patients and families complain about care. (November 2018) - Adams, Mary; Maben, Jill; Robert, Glenn
This article draws from sociological and socio-legal studies of dispute between patients and doctors to examine how healthcare professionals made sense of patients' complaints about healthcare. We analyse 41 discursive interviews with professional healthcare staff working in eight different English National Health Service settings to explore how they made sense of events of complaint and of patients' (including families') motives for complaining. We find that for our interviewees, events of patients' complaining about care were perceived as a breach in fundamental relationships involving patients' trust or patients' recognition of their work efforts. We find that interviewees rationalised patients' motives for complaining in ways that marginalised the content of their concerns. Complaints were most often discussed as coming from patients who were inexpert, distressed or advantage-seeking; accordingly, care professionals hearing their concerns about care positioned themselves as informed decision-makers, empathic listeners or service gate-keepers. We find differences in our interviewees' rationalisation of patients' complaining about care to be related to local service contingences rather than to fixed professional differences. We note that it was rare for interviewees to describe complaints raised by patients as grounds for improving the quality of care. Our findings indicate that recent health policy directives promoting a view of complaints as learning opportunities from critical patient/consumers must account for sociological factors that inform both how the agency of patients is envisaged and how professionalism exercised contemporary healthcare work.